2017
DOI: 10.1590/1807-1929/agriambi.v21n9p606-610
|View full text |Cite
|
Sign up to set email alerts
|

Strategies of fertigation with saline water for growing cucumber in a greenhouse

Abstract: A B S T R A C TThe objective of this study was to evaluate the use of saline water to grow cucumbers cultivated in substrate composed of coconut fiber and washed fine sand (1:1) and submitted to splitroot system. The experimental design was completely randomized, with eight treatments and four replicates. Treatments consisted of different fertigation managements, comprising two nutrient solutions of different electrical conductivities (1.65 and 6.25 dS m -1 ), applied in a continuous or alternated way, with sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
3
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 18 publications
3
3
0
2
Order By: Relevance
“…In general, the results presented in this study on the splitroot technique as irrigation management to mitigate the effect of salinity on bell pepper growth and yield confirm those reported by other authors, in crops such as tomato (Koushafar et al, 2011;Guedes et al, 2015) and cucumber (Oliveira et al, 2017).…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…In general, the results presented in this study on the splitroot technique as irrigation management to mitigate the effect of salinity on bell pepper growth and yield confirm those reported by other authors, in crops such as tomato (Koushafar et al, 2011;Guedes et al, 2015) and cucumber (Oliveira et al, 2017).…”
Section: Resultssupporting
confidence: 90%
“…Similar results have been found by Attia et al (2009), Guedes et al (2015 and Oliveira et al (2017), who worked with pea tomato and cucumber, respectively, under two salinity levels and using the split-root method. These authors observed that root exposure to salinity led to decrease in biomass production, and that the negative effect of salinity was mitigated when plants were cultivated with only half of the root system irrigated with saline water, whereas the other half was irrigated with the low-salinity control treatment.…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…O pepino tem crescido em importância na comercialização de hortaliças, muito apreciado e consumido em todo Brasil (OLIVEIRA et al, 2017). Sendo produto perecível e consumido in natura, na forma de saladas, onde a preocupação com a qualidade nutricional do pepino deve ser mantida em todos os seguimentos envolvidos no processo da produção e comercialização.…”
Section: Introductionunclassified
“…Medeiros et al (2010) analisaram diferentes níveis de salinidade na produção de pepino em cultivo protegido, encontrando as maiores médias de produção total com a condutividade elétrica da solução do solo próxima de 4 dS m -1 ; porém, houve uma queda na produtividade para níveis de salinidade acima do reportado. Oliveira et al (2017) trabalharam com uma prática de manejo de divisão de raízes, quando a mesma planta tem a sua raiz dividida em dois ambientes separados fisicamente.…”
Section: Nos Estudos Deunclassified